2015
DOI: 10.1002/sce.21175
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Descriptive Science of Teaching: How the TDOP Illuminates the Multidimensional Nature of Active Learning in Postsecondary Classrooms

Abstract: Detailed accounts of teaching can shed light on the nature and prevalence of active learning, yet common approaches reduce teaching to unidimensional descriptors or binary categorizations. In this paper, I use the instructional systems‐of‐practice framework and the Teaching Dimensions Observation Protocol (TDOP) to advance an approach to thinking about teaching in science classrooms in more multidimensional terms. Using descriptive statistics and social network analysis, I examine the teaching practices employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 66 publications
2
65
0
Order By: Relevance
“…With both protocols, trained observers document student and instructor activities during each 2 minute time interval of an observed class period (Hora and Ferrare, 2013;Smith et al, 2014) by coding for occurrences of specific student and teacher behaviors (Hora and Ferrare, 2013;Smith et al, 2013). The TDOP has 33 possible activities to code in 5 categories (Hora, 2015), which are reduced to 25 elements in the COPUS. Similarly, the Practical Observation Rubric to Assess Active Learning (PORTAAL) was developed from discipline-based education research to capture evidence of students engaged in research-based elements of active learning in observed STEM classrooms (Eddy et al, 2015).…”
Section: Common Observation Protocols Used In Stem Disciplinesmentioning
confidence: 99%
See 1 more Smart Citation
“…With both protocols, trained observers document student and instructor activities during each 2 minute time interval of an observed class period (Hora and Ferrare, 2013;Smith et al, 2014) by coding for occurrences of specific student and teacher behaviors (Hora and Ferrare, 2013;Smith et al, 2013). The TDOP has 33 possible activities to code in 5 categories (Hora, 2015), which are reduced to 25 elements in the COPUS. Similarly, the Practical Observation Rubric to Assess Active Learning (PORTAAL) was developed from discipline-based education research to capture evidence of students engaged in research-based elements of active learning in observed STEM classrooms (Eddy et al, 2015).…”
Section: Common Observation Protocols Used In Stem Disciplinesmentioning
confidence: 99%
“…While the three instructional category labels, Student Centered, Transitional, and Teacher Centered (Budd et al, 2013), have been criticized as being value laden (e.g., Hora, 2015), they are already in use, and therefore we use them here to avoid inventing new category titles that may cause confusion. The Transitional category is used only to indicate that the RTOP score is intermediate between the Teacher Centered and Student Centered categories (Budd et al, 2013), and does not suggest that an instructor is attempting to pass through this category to get to another.…”
Section: Classroom Observationsmentioning
confidence: 99%
“…In an attempt to gain a more quantifiable understanding of the quite different learning dynamics and student-teacher interactions which presented themselves so readily perceivable in the different types of laboratory classes, we attempted to capture the interaction learning pattern in the class using the Dimensions Observation Protocol (TDOP) tool developed by Hora [21]. The TDOP tool captures instructional practices, student-teacher interactions, and instructional technology through minute, direct observations and recording of the presence of key activities within the class room.…”
Section: Dynamics Of Laboratory Learning Experiencesmentioning
confidence: 99%
“…While these definitions may be useful for differentiating pedagogies which are essentially reformed in nature from those that take a more traditional, didactic approach, they have been criticized for describing teaching in binary terms [5]. They are also rather broad, encompassing a range of activity types.…”
Section: Introductionmentioning
confidence: 99%